Prenatal Lung Morphogenesis and Prerequisites for the Development of Respiratory Distress Syndrome in Premature Neonates - S. A. Perepelitsa; A. M. Golubev; V. V. Moroz; M. A. Shmakova (Общая реаниматология)
This paper gives information on intrauterine lung development in health and under poor conditions influencing the prenatal morphogenesis of lung tissue: threatening miscarriage, gestosis in the first and second halves of pregnancy, and placental insufficiency. It considers the development of the lung depending on fetal gender and a season. Key words: premature delivery, prenatal lung morphogenesis, premature neonates, surfactant, respiratory distress syndrome.